2016
DOI: 10.1111/1440-1630.12350
|View full text |Cite
|
Sign up to set email alerts
|

Community integration outcomes of people with spinal cord injury and multiple matched controls: A pilot study

Abstract: This cohort of SCI participants was less integrated into home and productive occupations than matched norms, holding implications for planning and allocation of supports to influence outcomes within an NDIS. Further research is necessary to understand community integration outcomes in larger matched samples.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…The current study found that community integration was a positive factor associated with physical (30) and WHOQOL-DIS module QoL. However, literature review found that the CIQ score of Chinese adults with cSCI was lower than that of community-dwelling adults with SCI in Australia (41) and Bangladesh (42). More active interventions are needed to improve community integration among individuals with cSCI (43).…”
Section: Discussionmentioning
confidence: 61%
“…The current study found that community integration was a positive factor associated with physical (30) and WHOQOL-DIS module QoL. However, literature review found that the CIQ score of Chinese adults with cSCI was lower than that of community-dwelling adults with SCI in Australia (41) and Bangladesh (42). More active interventions are needed to improve community integration among individuals with cSCI (43).…”
Section: Discussionmentioning
confidence: 61%
“…One third participants were not satisfied about their acceptance in community. It was found that greater levels of social support and peer mentoring can improve long term outcome of SCI [24]. Greater life satisfaction has been documented when people with SCI were involved in productive activities, such as work, leisure, and education 8 is associated with community reintegration [19].…”
Section: Discussionmentioning
confidence: 99%
“…The CIQ-R is an 18-item questionnaire designed to be a brief, reliable measure of home, social, productivity integration, and electronic social networking, designed at first to be administered to people with TBI [ 12 14 , 45 47 ]. In recent times, it has also been used to assess people with SCI [ 3 , 15 , 24 , 48 ] and other physical disability [ 16 ], aphasia [ 8 , 49 ], brain tumours [ 17 ], and burn injuries [ 50 ], as well as young people with a range of acquired and congenital disabilities who are living in nursing homes for the elderly [ 51 ].…”
Section: Methodsmentioning
confidence: 99%